Development of Alginate Microspheres Containing Chuanxiong for Oral Administration to Adult Zebrafish. (15th June 2016) - Lin, Li-Jen; Chiang, Chung-Jen; Chao, Yun-Peng; Wang, Shulhn-Der; Chiou, Yu-Ting; Wang, Han-Yu; Kao, Shung-Te
Abstract : Oral administration of Traditional Chinese Medicine (TCM) by patients is the common way to treat health problems. Zebrafish emerges as an excellent animal model for the pharmacology investigation. However, the oral delivery system of TCM in zebrafish has not been established so far. This issue was addressed by development of alginate microparticles for oral delivery of chuanxiong, a TCM that displays antifibrotic and antiproliferative effects on hepatocytes. The delivery microparticles were prepared from gelification of alginate containing various levels of chuanxiong. The chuanxiong-encapsulated alginate microparticles were characterized for their solubility, structure, encapsulation efficiency, the cargo release profile, and digestion in gastrointestinal tract of zebrafish. Encapsulation of chuanxiong resulted in more compact structure and the smaller size of microparticles. The release rate of chuanxiong increased for alginate microparticles carrying more chuanxiong in simulated intestinal fluid. This remarkable feature ensures the controlled release of encapsulated cargos in the gastrointestinal tract of zebrafish. Moreover, chuanxiong-loaded alginate microparticles were moved to the end of gastrointestinal tract after oral administration for 6 hr and excreted from the body after 16 hr. Therefore, our developed method for oral administration of TCM in zebrafish is useful for easy and rapid evaluation of the drug effect on disease.